Design, synthesis and evaluation of 2-aryl benzoxazoles as promising hit for the A2A receptor. (1st January 2017) - Duroux, Romain; Renault, Nicolas; Cuelho, Joana Esteves; Agouridas, Laurence; Blum, David; Lopes, Luisa V.; Melnyk, Patricia; Yous, Saïd
Abstract: The development of adenosine A2A receptor antagonists has received much interest in recent years for the treatment of neurodegenerative diseases. Based on docking studies, a new series of 2-arylbenzoxazoles has been identified as potential A2A R antagonists. Structure-affinity relationship was investigated in position 2, 5 and 6 of the benzoxazole heterocycle leading to compounds with a micromolar affinity towards the A2A receptor. Compound F1, with an affinity of 1 μm, presented good absorption, distribution, metabolism and excretion properties with an excellent aqueous solubility (184 μm) without being cytotoxic at 100 μm. This compound, along with low-molecular weight compound D1 ( Ki = 10 μm), can be easily modulated and thus considered as relevant starting points for further hit-to-lead optimisation.